2014
DOI: 10.1016/j.bbamem.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cysteine residues are necessary for sorting and transport activity of the arsenite permease Acr3p from Saccharomyces cerevisiae

Abstract: The yeast transporter Acr3p is a low affinity As(III)/H(+) and Sb(III)/H(+) antiporter located in the plasma membrane. It has been shown for bacterial Acr3 proteins that just a single cysteine residue, which is located in the middle of the fourth transmembrane region and conserved in all members of the Acr3 family, is essential for As(III) transport activity. Here, we report a systematic mutational analysis of all nine cysteine residues present in the Saccharomyces cerevisiae Acr3p. We found that mutagenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…S17 to arsenic would be the reduction of arsenate to arsenite and subsequent extrusion through membrane pumps as ArsB and Acr3 (Figure 7). Acr3 presents the conserved residues required for functionality as observed by Aaltonen and Silow (2008), Fu et al (2009), andMaciaszczyk-Dziubinska et al (2014) and would confer high resistance to arsenite (As [III]). Also, other mechanisms that overcome oxidative stress caused by arsenic would also help in the resistance to the metalloid.…”
Section: Discussionmentioning
confidence: 99%
“…S17 to arsenic would be the reduction of arsenate to arsenite and subsequent extrusion through membrane pumps as ArsB and Acr3 (Figure 7). Acr3 presents the conserved residues required for functionality as observed by Aaltonen and Silow (2008), Fu et al (2009), andMaciaszczyk-Dziubinska et al (2014) and would confer high resistance to arsenite (As [III]). Also, other mechanisms that overcome oxidative stress caused by arsenic would also help in the resistance to the metalloid.…”
Section: Discussionmentioning
confidence: 99%
“…S-acylation of telomere-binding protein Rif1 anchored it to the inner nuclear membrane, which influences its role in heterochromatin dynamics (Park et al, 2011). Mutagenesis of cysteine in different positions of Arsenite permease Acr3p can cause its completely or partially dysfunction as a low affinity As(III)/H + and Sb(III)/H + antiporter, and Cys90 which localizes in the cytosolic loop but in close proximity to transmembrane regions has the high possibility to be S-acylated (Maciaszczyk-Dziubinska et al, 2014). It was also reported that S-acylation is necessary for the export of chitin synthase Chs3 from ER (Lam et al, 2006).…”
Section: S-acylationmentioning
confidence: 99%
“…Following our previous characterization of the yeast Acr3p (Maciaszczyk-Dziubinska et al, 2014), we aimed to identify additional residues that are engaged in the As(III)/H + exchange. We hypothesized that conserved hydrophilic residues located in putative transmembrane regions of the yeast Acr3p might be involved in the As(III)/H + antiport.…”
Section: Construction Of Acr3 Allelesmentioning
confidence: 99%
“…The Acr3 family of arsenite transporters represents the most common pathway conferring high-level resistance to toxic metalloids (Rosen and Tamás, 2010;Maciaszczyk-Dziubinska et al, 2012). Members of the Acr3 family are present in bacteria, archaea, unicellular eukaryotes, fungi and lower plants but have been lost in flowering plants and animals (Fu et al, 2009;Indriolo et al, 2010;Maciaszczyk-Dziubinska et al, 2014). However, yeast or fern Acr3 can be successfully expressed in rice and Arabidopsis thaliana, leading to increased tolerance to arsenicals (Ali et al, 2012;Duan et al, 2012;Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation